Tinjauan Teoritis Kurikulum Pendidikan Agama Islam untuk Anak Usia Dini - Mutholingah, Siti; Handoko (STAI Ma'had Aly Al-Hikam Malang, 2024)
The aims of this research are: (1) to analyze the concept of Early Childhood, (2) to analyze the Islamic Religious Education curriculum for early childhood, (3) to analyze the implementation of the PAI curriculum for early childhood in Play Groups and Kindergarten. This study uses a literature review or what is called a literature study. The results of this study are: (1) Early Childhood are children aged 0-6 years, where early childhood education is a form of education that focuses on laying the foundation for physical growth and motor skills development, rough, creative intelligence, emotional intelligence, plural intelligence and spiritual intelligence, (2) The Islamic Religious Education Curriculum in early childhood is a set of plans and arrangements regarding objectives, content and learning materials as well as methods used as guidelines organizing physical and spiritual guidance activities for early childhood based on Islamic religious laws in order to prepare the Muslim generation to understand, appreciate and practice the teachings of the Islamic religion which they believe in thoroughly, (3) implementation of the Islamic education curriculum for early childhood, namely in The form of the play activity program is implemented in accordance with the child-centered curriculum and can support learning and development activities in every aspect, including aesthetic, cognitive, emotional, language, physical and social. The findings from this research are that the Islamic education curriculum in early childhood education must be results-oriented and link various concepts and early childhood development.